Design of ultra low‐power RF oscillators based on the inversion coefficient methodology using BSIM6 model. (26th March 2015) - Guitton, G.; Mangla, A.; Chalkiadaki, M.‐A.; Fadhuile, F.; Taris, T.; Enz, C.
Summary: This paper presents a fast and accurate way to design and optimize LC oscillators using the inversion coefficient ( IC ). This methodology consists of four steps: linear analysis, nonlinear analysis, phase noise analysis, and optimization using a figure of merit. For given amplitude of oscillation and frequency, we are able to determine all the design variables in order to get the best trade‐off between current consumption and phase noise. This methodology is demonstrated through the design of Pierce and cross‐coupled oscillators and has been verified with BSIM6 metal oxide semiconductor field effect transistor compact model using the parameters of a commercial advanced 40 nm complementary metal oxide semiconductor process. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : This paper presents a fast and accurate way to design and optimize LC oscillators using the inversion coefficient. For given amplitude of oscillation and frequency, we are able to determine all the design variables in order to get the best tradeoff between current consumption and phase noise. This methodology is demonstrated through the design of Pierce and Cross‐Coupled oscillators and has been verified with BSIM6 MOSFET compact model using the parameters of a commercial advanced 40‐nm CMOS process.